Analysis of Sharia Economic Law on Video Reupload Practices by Facebook Fanpages User - Muhajir Muhajir; Zaenul Haq (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
Facebook Fanspage is a feature on Facebook widely used by brands to build their community in cyberspace. Facebook currently has provided a Facebook Fanspage feature where users can upload any type of video, not even a few of the users who get rewards or fees from uploading videos on the Facebook Fanspage page. However, it does not mean that it is without problems, one of the problems that still occurs on Facebook Fanspage is that many cases of copyright infringement on the site, such as the practice of re-uploading for example. The study examines how the validity of income obtained from reuploading activities is viewed from the perspective of ibtikar right in sharia economic law. The research is a type of field research. The results of the research are that it is illegal to reupload videos carried out solely for personal gain without giving royalties to the producer/ related label. In other words, the act is the same as a merchant selling goods belonging to someone else without the permission of the owner. Copyright in Islam is known as the ibtikar right which is a copyright attached to the owner of the original video and part of intellectual property, both material and immaterial. Thus, it must be legally protected. Islam highly respects copyright as a personal property right so that the right of ibtikar is included in the Maqashid Sharia to maintain the existence of property ownership of every Muslim. Every property that results from the act of reuploading videos in Islam is unlawful, because it is included in violating the rights of others. Keywords: Ibtikar right, Facebook, Facebook Fanspage, Reward